Epidemiology of Antibiotic Multidrug Resistant genes in Gram Negative Bacteria among Symptomatic Patients with Bacteriuria Attending Federal Medical Center Yenagoa Bayelsa State Nigeria - O, Oburu V.; V, Anyiam I. (Darul Yasin Al Sys, 2025)
The global rise in antibiotic resistance among Gram-negative bacteria poses a significant threat to public health, particularly in resource-limited settings. This study investigates the epidemiology of multidrug-resistant (MDR) genes in Gram-negative bacteria isolated from symptomatic patients with bacteriuria at the Federal Medical Center Yenagoa, Bayelsa State, Nigeria. A total of 100 urine specimens were collected from patients within the age range of 13 to 70 years attending Federal Medical Centre Yenagoa. The specimens were analyzed by culture, biochemical tests, and molecular methods. The Antibiotic susceptibility test was done using the Kirby-Bauer disc diffusion method following clinical and laboratory standard institute (CLSI) guidelines. The results showed that 26 bacterial isolates were obtained which include; Escherichia coli 14(53.8%), Klebsiella pneumoniae 6(23.1%), Proteus mirabilis 4 (15.4%), and Pseudomonas aeruginosa 2(7.7%). The highest occurring isolate was E. coli 14(53.8%) while the lowest was P. aeruginosa 2(7.7%). E. coli is the predominant isolate in females 9(34.6%). Female had the highest occurring isolates 14(53.5%) compared to male 12(46.1%). The age ranges with the highest isolates was 51-60 years and 61-70 years with 7(26.9%) respectively, while the lowest was within the age range of 13-20 years with 1(3.8%). The antibiotic susceptibility tests revealed that E. coli showed the highest resistance to ampicillin (85.7%), ceftriaxone (78.57%), piperacillin/tazobactam (64.28%), and cotrimoxazole (64.28%), with notable susceptibility to ciprofloxacin (57.14%) and levofloxacin. K. pneumoniae demonstrated strong resistance to ampicillin and piperacillin/tazobactam at 83.33% respectively, while being most susceptible to ciprofloxacin, gentamicin, and azithromycin at 66.7% respectively. P. mirabilis exhibited high resistance to ceftriaxone, tetracycline, and azithromycin (75%) respectively, but showed maximum susceptibility to piperacillin/tazobactam, ciprofloxacin, gentamicin, and levofloxacin (75%) respectively. P. aeruginosa was most resistant and completely susceptible to multiple antibiotics at 50% and 100%. The resistance genes CTX-M and SHV were present in P. mirabilis while TEM was absent. CTX-M, SHV and TEM were not present in E. coli, K. pneumoniae, and P. aeruginosa. The 16S rRNA of the isolates showed a percentage similarity to other species at 100%. The evolutionary distances computed using the Jukes-Cantor method were in agreement with the phylogenetic placement of the 16S rRNA of the isolates within the E. coli, Klebsiella, Pseudomonas, and Providencia sp., and revealed a close relatedness to the E. coli, K. pneumoniae, P. aeruginosa, and Providencia stuartii. In conclusion, the observed antibiogram profile revealed multidrug resistance among the isolated bacteria and at the same time pathogenic. Therefore, it is recommended to conduct comprehensive surveillance, investigate risk factors, utilize molecular techniques, evaluate antimicrobial stewardship, and promote one health approach to prevent bacteriuria.